An Analysis of EFL Students’ Reading Ability at SMA Pembangunan Padang - Alisya Isra Belinda; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
This study aimed to describe the students’ reading ability and the causes of problems in reading English at SMA Pembangunan Padang. The population of this research was the 12th grade of natural science students of SMA Pembangunan Padang consist of 92 students. The sample was taken through proportional random sampling and the number was 30 students. The instruments of this research were the reading test and interview. Result of the analysis showed that the students’ reading abilities were at in inadequate and failing category and they have problems with determining main idea, making inference, reference, understanding vocabulary, detail information, factual and negative factual information. Then, the factors that cause their reading problems are literal comprehension (trouble in identifying the main idea from a long text and the location of main idea, trouble in differentiating the main idea from the supporting details), inferential comprehension (trouble in understanding the content of the text and figure the conclusion of the text), vocabulary knowledge (vocabulary limitation, don't understand pronouns), critical thinking (trouble in understanding implied information, hard to determine the information referred to in a pronoun, trouble in determine which statement is true or false), and classroom environment that dealt with quality of teaching (teacher doesn’t teach new vocabulary specifically and unclear explanation to help them able to make the inference). The findings suggest pedagogical implications for the promoting the EFL learners’ reading ability.